Recommendations for pathologic staging (pTNM) of cancer of the esophagus and esophagogastric junction for the 8th edition AJCC/UICC staging manuals. Issue 8 (1st December 2016) - Rice, T. W.; Ishwaran, H.; Hofstetter, W. L.; Kelsen, D. P.; Apperson‐Hansen, C.; Blackstone, E. H.; ,
SUMMARY: We report analytic and consensus processes that produced recommendations for pathologic stage groups (pTNM) of esophageal and esophagogastric junction cancer for the AJCC/UICC cancer staging manuals, 8th edition. The Worldwide Esophageal Cancer Collaboration provided data for 22, 654 patients with epithelial esophageal cancers; 13, 300 without preoperative therapy had pathologic assessment after esophagectomy or endoscopic treatment. Risk‐adjusted survival for each patient was developed using random survival forest analysis to identify data‐driven pathologic stage groups wherein survival decreased monotonically with increasing group, was distinctive between groups, and homogeneous within groups. The AJCC Upper GI Task Force, by smoothing, simplifying, expanding, and assessing clinical applicability, produced consensus pathologic stage groups . For pT1‐3N0M0 squamous cell carcinoma (SCC) and pT1‐2N0M0 adenocarcinoma, pT was inadequate for grouping; subcategorizing pT1 and adding histologic grade enhanced staging; cancer location improved SCC staging. Consensus eliminated location for pT2N0M0 and pT3N0M0G1 SCC groups, and despite similar survival, restricted stage 0 to pTis, excluding pT1aN0M0G1. Metastases markedly reduced survival; pT, pN, and pM sufficiently grouped advanced cancers. Stage IIA and IIB had different compositions for SCC and adenocarcinoma, but similar survival. Consensus stage IV subgrouping acknowledged pT4N+ and pN3 cancers had poor survival, similar to pM1. Anatomic pathologic stage grouping, based on pTNM only, produced identical consensus stage groups for SCC and adenocarcinoma at the cost of homogeneity in early groups. Pathologic staging can neither direct pre‐treatment decisions nor aid in prognostication for treatment other than esophagectomy or endoscopic therapy. However, it provides a clean, single therapy reference point for esophageal cancer.